Examining NCT Dream’s Influence as a Celebrity Endorser on Consumer Purchase Intention: The Mediating Role of Brand Image - Maria , Angelina Earlene Ave; Maria , Angelita Nabeela Ave; Proboyo, Adelina (Review of Management and Entrepreneurship, 2025)
Marketers globally are leveraging celebrity endorsers to boost their business, with many Indonesian companies turning to Korean celebrities as endorsers for their products. The aims of this study are to examines the impact of NCT Dream as a celebrity endorser on consumer purchase intention for Tos-Tos snacks. The effectiveness of the celebrity endorser will be evaluated using the TEARS model, which includes trustworthiness, expertise, attractiveness, respect, and similarity. Additionally, the study investigates the mediating role of brand image on the relationship between celebrity endorsement and purchase intention. This study employed a quantitative research method, utilizing questionnaires for data collection, and 100 respondents meeting the criteria were analyzed using statistical procedures. One hundred data from qualified respondents was collected via questionnaires distributed through simple random sampling. The results reveal significant relationships between respect and purchase intention and between brand image and purchase intention. Furthermore, an insignificant relationship happens between trustworthiness, expertise, attractiveness, and similarity and purchase intention. Lastly, the result also shows that brand image mediates the relationship between expertise and purchase intention.